Implementing Local Content Curriculum in Schools and Madrasahs: Challenges and Opportunities - Abdul Hamid; Ari Susanto (Al-Qalam Institue, 2026)
The local content curriculum is a curricular program designed to integrate regional potential, needs, and socio-cultural characteristics into the educational process. This study aims to examine the role and implementation of the local content curriculum in supporting the preservation of local culture and the development of students’ contextual knowledge and skills. The research employed a qualitative approach through literature review and analysis of relevant educational policies and practices related to the implementation of local content learning in schools and madrasahs. The findings indicate that the local content curriculum plays a significant role in introducing regional languages, arts, and traditional crafts, while also fostering students’ cultural awareness and strengthening their sense of identity within the national cultural framework. Furthermore, the implementation of local content learning provides opportunities for students to develop knowledge, attitudes, and skills that are closely related to the potential and needs of their local environment. The study implies that strengthening the implementation of the local content curriculum is essential for promoting culturally responsive education and supporting the preservation of local cultural heritage within the national education system.